Infestation of Anthonomus grandis (Coleoptera: Curculionidae) on re-sprout of cotton plants - Grigolli, José Fernando Jurca (2015)
The destruction of cotton crop residues at the end of the crop cycle is a key strategy for the phytosanitary crop management, since its off-season re-sprout can provide sites for feeding and oviposition of pests such as the boll weevil. This study aimed to evaluate the re-sprout capacity of cotton cultivars, as well as their infestation by Anthonomus grandis. A randomized blocks design, in a 3 x 2 factorial arrangement, with three cultivars (FM 910, DeltaOPAL and NuOPAL), two mowing heights (10 cm and 20 cm) and four replications, was used. Weekly evaluations were carried out for measuring the percentage of plant re-sprout for both mowing heights, percentage of flower buds infested by the boll weevil and number of adults per re-sprout. Plants mowed at 10 cm presented a lower sprout capacity and consequently less flower buds, reducing the boll weevil population density in the area, while plants mowed at 20 cm showed high re-sprouts rates, seven days after mowing. The FM 910 cultivar had the highest number of re-sprout plants, while the DeltaOPAL cultivar showed the highest number of flower buds and adults per plant, as well as the highest percentage of buds damaged by the boll weevil.